Enhancement of Antimicrobial and Antiproliferative Activities of Standardized Frankincense Extract Using Optimized Self-Nanoemulsifying Delivery System - Shereen S. El-Mancy; Alaadin E. El-Haddad; Walaa A. Alshareef; Amr M. Saadeldeen; Soad Z. El-Emam; Osama S. Elnahas (MDPI AG, 2021)
Boswellic acids (BAs) are the main bioactive compounds of frankincense, a natural resin obtained from the genus Boswellia. This study aimed to develop a self-nanoemulsifying delivery system (SNEDS) to improve the antimicrobial and antiproliferative activities of standardized frankincense extract (Fr-extract). Fr-extract was standardized, and BA content was quantified using the developed HPLC-UV method. Screening studies of excipients followed by formula optimization using a mixture simplex lattice design was employed. The optimized Fr-SENDS formulation was characterized. Furthermore, microbiological and antiproliferative assessments of the standardized Fr-extract and Fr-SNEDS were evaluated. Quantification demonstrated that the major constituent is 11-keto-boswellic acid (KBA) (16.25%) among BA content (44.96%). The optimized Fr-SENDS (composed of 5% CapryolTM 90, 48.7% Gelucire® 44/14 and 46.3% ethanol) showed spherical nanosized dispersions with DS, PDI, and zeta potential of 17.9 nm, 0.2, and −14.5 mV, respectively. Fr-SNEDS exhibited lower MIC and MBC values compared with Fr-extract against pathogens conjugated with lung cancer and was comparable to reference antimicrobials. Fr-SNEDS showed superior antiproliferative activity over Fr-extract, with IC50 values of 20.49 and 109.5 μg mL−1, respectively. In conclusion, the optimized Fr-SNEDS could be easily developed and manufactured at a low cost and the in vitro results support its use as a potential adjuvant oral therapy for lung cancer. Further in vivo studies could be continued to assess the therapeutic efficiency of the prepared system.